Case Study : Alias Batik & Trading “Semi Automatic Canting Pen” / Noor Syafiqah Nordin - Nordin, Noor Syafiqah (2020)
The company has run for about 46 year when it started at 1971 which form by Alias Mohd Salleh one of the children of Mohd Salleh which is a former owner of the company which located at Kota Bharu, Kelantan. This company also have faced certain issues such as the weather condition to produce the batik and the old building facilities which had limit the production activities. The company is a manufacturing company where a variety of design of batik clothes and fabric are produced. The product is made by cotton cloth which have the length of 4 meters longs (depend on the customer how long the cloth) respectively and depends also to the demand of the customer whether the design is custom – made or ready – made and also the price of each unit is sold at RM 100. The quality of the product is preserve since the company practice quality management control and the design is improved by came up a new design every month with copyright to ensure no copy – cat or duplication happen in the future. The business hour of the company starts from 8 am until 5 p.m. from Monday to Saturday except on public holiday